2011
DOI: 10.1200/jco.2011.29.7_suppl.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EGFR inhibition with cetuximab on the efficacy of paclitaxel in previously treated metastatic urothelial cancer.

Abstract: 243 Background: The benefit of salvage chemotherapy such as weekly paclitaxel (TAX) is modest in metastatic (met) urothelial ca, with median TTP of ≤3 months and ORR of 10% (95% CI 4-18% [combined results, Vaughn 2002; Joly, 2009]). Cetuximab (CET) is a monoclonal antibody against the epidermal growth factor receptor (EGFR). High-grade urothelial cancer overexpress EGFR. We conducted a multicenter randomized, noncomparative phase II study to measure the efficacy of CET ± TAX in patients (pts) with previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Furthermore, targeted agents combined with a cytotoxic drug (paclitaxel + cetuximab or docetaxel + vandetanib) in platinum-pretreated patients did not demonstrate additive activity and resulted in increased toxicities [94] , [95] .…”
Section: Perspectives For the Future Of Uc Joaquim Bellmunt Spainmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, targeted agents combined with a cytotoxic drug (paclitaxel + cetuximab or docetaxel + vandetanib) in platinum-pretreated patients did not demonstrate additive activity and resulted in increased toxicities [94] , [95] .…”
Section: Perspectives For the Future Of Uc Joaquim Bellmunt Spainmentioning
confidence: 96%
“…Several single-agent phase II studies have tested targeted therapies in the second-line setting, but none have shown substantial activity. Trials are also testing targeted agents combined with a cytotoxic drug (paclitaxel + cetuximab or docetaxel + vandetanib), but the combinations exacerbated toxicity, and no synergistic or additive effects were reported [94] , [95] . More recent attempts at combining targeted agents with cytotoxic drugs have been more encouraging (docetaxel + ramucirumab versus docetaxel), based on the results of a phase II trial, although toxicity was increased in the combination arm [96] .…”
Section: Challenging Patient Profiles and ‘Unfit’ Patients In Advancementioning
confidence: 99%
“…Cetuximab is a chimeric (mouse/human) monoclonal antibody for blocking EGFR signaling. A phase II clinical trial [ 38 ] of 39 pretreated patients with metastatic urothelial carcinoma demonstrated that combined cetuximab and paclitaxel chemotherapy yielded a better response rate (28.5%) than did cetuximab monotherapy, in which 9 of 11 patients had disease progression at 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Grade 3 adverse events occurring in more than two patients were rash ( n =5), fatigue ( n =4), anemia ( n =4), and low magnesium ( n =3). This study showed that EGFR inhibition with cetuximab appears to augment the antitumor activity of paclitaxel in patients with previously treated urothelial cancers, warranting further study [19]. Cetuximab is also being examined in front-line setting in combination with GC in a study for which accrual is complete and results are awaited [20].…”
Section: Targeted Therapymentioning
confidence: 99%